THE PHENOMENON OF JUMBO ANIMATED FILMS AS A MEDIUM FOR REFLECTING MORAL AND SOCIAL VALUES IN PRIMARY EDUCATION (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the representation of moral and social values in the animated film Jumbo and analyze its relevance to the character development of elementary school students. In addition, this study explains the potential use of this film as a medium for reflecting on values in learning. The research method used is qualitative with content analysis and documentation techniques through in-depth observation of the storyline, scenes, dialogue, and visual symbols in Ryan Adriandhy's film Jumbo. The results show that the film Jumbo represents five main values, namely courage, empathy, friendship, responsibility, and self-confidence. These values are conveyed through the dynamics of Don's conflicts and his interactions with other characters, which are relevant to the moral and social development needs of elementary school students. This film has strong potential as a medium for reflection through targeted screening strategies, reflective discussions, and follow-up activities such as mini-dramas and reflective journals. Thus, the film Jumbo not only serves as entertainment but also as a medium for learning contextual, interesting, and easily integrated character values in elementary education.